The positive effect of mother-performed infant massage on infantile eczema and maternal mental state: A randomized controlled trial - Lin, Lin; Yu, Lin; Zhang, Shuying; Liu, Jing; Xiong, Ying (Frontiers in Public Health, 2023)
Objective To observe the influence of MPIM on infantile eczema, quality of life, growth and maternal mental state. Methods This trial was a randomized controlled study. Sixty-six full-term infants with eczema were randomly divided into eczema control group (EC group, n = 33) and eczema with MPIM group (EM group, n = 33), along with healthy full-term infants in the healthy control group (HC group, n = 31). The mothers in the EC group received the instruction of routine care, while the mothers in the EM group applied massage on the infants plus receiving the same instruction of the routine care. HC group received none of any specific intervention. Data were collected in the three groups at the baseline and at the end of 2- and 5-month intervention. Before and at the end of 2-month intervention, the following indexes were investigated in infants including the growth indexes, eczema area severity index (EASI), infantile dermatitis quality of life index (IDQOL). And the scores of self-rating anxiety scale (SAS) and self-rating depression scale (SDS) were investigated in mothers at the same timepoints. At the end of 5-month intervention, the infants' growth and relapse condition of eczema were observed. Results Overall, 31 cases in HC group, 31 in EC group and 32 in EM group were included for data analysis. There were no significant differences in the indexes of infantile growth among the three groups (all P >0.05). The scores of EASI and IDQOL significantly lowered (both P < 0.001) in EC group following the instruction of routine care, along with reduced maternal scores of SAS and SDS (both P < 0.05). Compared with the EC group, the EM group showed significantly lower scores of EASI and IDQOL (both P < 0.001) and lower relapse rate (P < 0.01) in infants with eczema, along with significantly lower scores of SAS and SDS in mothers (both P < 0.01). Moreover, none of obvious adverse reaction was reported following MPIM, to which most of the mothers could adhere. Conclusion MPIM could effectively promote the remission of infantile eczema and reduce its relapse, along with relieving maternal anxiety and depression mood. Clinical trial registration Identifier: ChiCTR2200066246.